Leisure time physical activity and incident use of prescription tranquilizers: A longitudinal population-based study - Sheikh, Mashhood Ahmed (Journal of Affective Disorders, 2018)
Accepted manuscript version, licensed CC BY-NC-ND 4.0. Published version available at https://doi.org/10.1016/j.jad.2018.06.010 . Objective : Physical inactivity is a major public health problem associated with an increased risk of several psychiatric and physical conditions. This study investigated the association between leisure time physical activity (PA) and incident use of prescription tranquilizers in a regionally representative and prospective cohort. Methods : A total of 4043 men and women (mean age: 61.3 years; 57% women) from the Tromsø Study were followed for six years. Leisure time PA was captured at baseline. Psychiatric morbidity was measured by use of prescription tranquilizers, captured at both baseline and follow-up. Leisure time PA at baseline was used as a predictor of subsequent (incident) use of prescription tranquilizers. We used multinomial regression models and Poisson regression models to estimate relative risk-ratios (RRRs), and relative risks (RRs), respectively, and their corresponding 95% confidence intervals (CIs). Results : In the fully-adjusted model, accounting for socio-demographic factors, parental history of psychopathology, years of education, smoking, respondent's psychopathology at baseline, and occupational PA, a lower leisure time PA conferred a 41% increased risk of incident use of prescription tranquilizers at follow-up (RR = 1.41, 95% CI: 1.09, 1.83; p = 0.010). Conclusions : These findings suggest that physical inactivity increases the risk of psychiatric morbidity (albeit, measured via use of prescription tranquilizers). Future regionally representative and longitudinal research is required to confirm/refute our findings and explore underlying mechanisms.